Parental Challenges in Child Rearing within Islamic Guidance: A Descriptive Study - Mohamed Sulthan Ismiya Begum; Ismail Fathima Faneeka (Penerbit Hellow Pustaka, 2026)
Child rearing serves as the fundamental cornerstone of Islamic social development. A parent's primary responsibility involves nurturing faith, character, emotions, and intellect from early childhood, shaping children under the framework of religious guidance. However, in the contemporary era, parents encounter a multitude of complex challenges. Factors such as the influence of external global cultures, the pervasive impact of the digital world, diminishing parent-child communication, workplace stress, and economic constraints have created significant hurdles in the practice of effective parenting. Using a theoretical approach, this study examines the challenges faced by parents in child rearing through the lens of Islamic guidance. The methodology involves a qualitative analysis of primary sources, namely the Holy Qur'an and Sunnah, supplemented by secondary data including research articles, books, journals, and academic web resources. The primary objective of this research is to identify the specific obstacles parents encounter in the upbringing of their children. The findings reveal that parents grapple with challenges such as a lack of parenting experience, daily work-related stress, inflexible lifestyles, and the demanding nature of the long-term investment required for a child's future. The study concludes that adhering to Islamic principles and guidance in child rearing effectively reduces parental stress and provides an optimal framework for cultivating a healthy, responsible, and God-conscious generation.